From Court to Conquest: Unveiling the Challenges among Basketball Players in Sports Participation. A Case Study - Medina, Sachie D.; Medina, Daisy B.; Magdaong, Christian Dave Q.; Ong, Zandra Kathryn D.; Pabillaran, Bea Nadine M.; Pabillar, Dale Davies; Pacquiao, Jamaila O.; Pongao, Range V.; Quindo, Christine Nicole S.; Malalis, Jamaica S.; Longakit, Jet C.; Aliser, Johnlenon N. (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
This study explores the challenges experienced encountered among basketball players in tournament sports participation. The study employed a descriptive-exploratory case study approach. The researcher used semi-structured interviews and non-participatory observation to collect data from six basketball players who met the researcher's criteria. The finding’s revealed that the participants were challenged during tournament sports participation. The participants pointed out that during sports tournament participation, the participants revealed that some of their struggles were physical restraints, health conditions, such as injuries, not enough resting time, in-game pressure, and lack of communication. Results revealed that the presence of pressure, miscommunication of the team, and health conditions are their highly faced struggles during the game. The findings have proven that the challenges experienced by athletes undeniably affect their performance, which is also influenced by how they perceive situations in a competitive sports environment. This study highlights the importance of addressing both physical and mental health concerns to enhance player performance and team success in competitive sports environments.